Meningkatkan Keaktifan Belajar Siswa Dalam Pembelajaran Active Debate Tari Melalui Blended Learning - Supriatna, Cepi (Program Studi Pendidikan Tari FBS UNJ, 2021)
Active learning of students is certainly a goal in active learning in the classroom. Researchers observed the process and results of learning arts and culture at SMPN 1 Margaasih with the learning that students seemed to be actively creating the learning process. This learning applied by the teacher triggers students to be active and improve good communication. The model applied by the art teacher is a stundent active dabate model that trains students to express their opinions accompanied by reasons and learn to respect differences of opinion, the learning is applied through blended learning. The purpose of this study is to increase the thinking power and active learning of students in the subject of cultural arts and it is hoped that in learning through blended learning students are able to find reference sources on the internet to increase their knowledge. The study conducted by researchers used a qualitative approach to determine the process and results implemented by teachers at SMPN 1 Margaasih. The results of this study indicate that students' learning activities are optimal in the material presented by the arts and culture teacher and the teacher's teaching strategy is able to hone students' analytical skills and speak through constructive debates about a topic or problem with rules and procedures that encourage them to give their opinion on arguments with groups that are packaged in joint discussions through blended learning. The results of this study can be used as recommendations and alternatives for teachers in using learning models to create active learning for students in using information and communication in their learning strategies, and as an effort to improve the quality of teaching and learning.